A proposal of a new rotational-compliant joint with oil-hydraulic McKibben artificial muscles. (3rd May 2018) - Morita, Ryusuke; Nabae, Hiroyuki; Endo, Gen; Suzumori, Koichi
Abstract: Conventional hydraulic actuators can generate a strong force due to high pressure. However, most of them are heavy and hard because they are made of metal. It is difficult to use such actuators in robots required to be as light as possible. Moreover, the joint mechanisms of these actuators have problems with intrinsic safety and robustness because the compliance is acquired using delicate sensors and advanced controls. Therefore, we propose a new rotational-compliant mechanism that allows the coexistence of strong force and compliance. The proposed mechanism has compliance in an active rotational direction and in two directions orthogonal to it. To realize this mechanism, we have developed a Hydraulic Artificial Muscle (HAM), which is very lightweight and able to generate strong force. Furthermore, the HAM has compliance without any advanced control. By exploiting the characteristics of the HAM, the function of the proposed mechanism can be realized even in conditions of compact dimensions. In this paper, by constructing a simple experimental system that imitates the proposed mechanism, and by modeling it, we verify its compliance from both a theoretical and an experimental point of view. We demonstrate that the mechanism has compliance in the three rotational directions. Abstract :